THE MIDWIFERY CARE OF Mrs. F, IUD ACCEPTOR IN THE WORK AREA OF PEUKAN BADA COMMUNITY HEALTH CENTER, ACEH BESAR, IN 2025 - Sari, Annisa Fatika; Lajuna, Lia; Sriyanti, Cut (Journal of Midwifery and Community Health (JMCH), 2025)
Reproductive health includes physical, mental, and social well-being, which can be achieved through the family planning (KB) program. One of the recommended methods is the Intrauterine Contraceptive Device (IUD) as part of the Long-Term Contraceptive Method (MKJP). At the Pekan Bada Health Center in 2022, out of 1,407 fertile age couples (PUS), 11.9% used IUDs. Midwives play an essential role in increasing the scope of IUD use through promotive, preventive, curative, and rehabilitative services. Based on this, the author conducted this case study as a final assignment report entitled "Midwifery Care for IUD Acceptors in the Pekan Bada Health Center Work Area, Aceh Besar Regency." The purpose of this case report is to carry out midwifery care for Mrs F in the Peukan Bada Health Center Area, Aceh Besar Regency, and document it in the form of SOAP. The first care was carried out on February 16, 2025. After data collection was completed, it was found that the mother wanted to use an IUD. The results of the examination were within normal limits. Then the data analysis of P3 A0 Mrs. F aged 30 years old, a candidate for IUD acceptor, the condition is good and has been given care to the mother regarding the use of contraception and types of contraception, and also explained the side effects, effectiveness, and explanation of the use of IUD and the subject understands what is conveyed so that the mother is sure to have IUD installed. Further care will be provided at the mother's next visit, depending on the nature of the problem.